Inspiring and encouraging organisational knowledge sharing through religion - Abdul Rahman , Ramlee; Hassan, Basri (IIUM Press, 2008)
The implementation of knowledge management initiative in an organisation is not about excellence processes alone, it is also about inter-networking effects between various communications, procedures, norms and values in the organisation’s practices. It is about how the people in the organisation view and perceive the change plan for the organisation. Knowledge sharing is an essential influence on the success of any knowledge management initiative. The real sharing which is required is between employees and their co-workers. Tangible economic rewards seem to have immediate effect on motivation to share knowledge, but the result is temporary and will slowly lose its effectiveness. The willingness to share knowledge will decrease once the rewards are withdrawn. However, non-monetary rewards may not have the immediate effect but long-term impact on the motivation. Employees’ involvement in an organisation’s knowledge sharing practices can be due to enforcement by the management or merely for the sake of accomplishing certain personal missions and gains. It is not something long term and lasting. On the other hand, religion highlights the significance of knowledge in seeking answers to fundamental questions of life and the truth-centring faith and belief. Fulfilling one’s religious obligation might be the best motivation or alternative intrinsic enforcement to develop good habits and positive environment. This intrinsic drive coupled with the extrinsic supports of technologies and procedural effectiveness will definitely enhance the commitment of employees to share knowledge. This paper attempts to discuss the issue of knowledge sharing in organisations, employees’ motivation to share knowledge and whether one’s religious conviction, faith and beliefs would contribute to the willingness and obligation to share knowledge.